OP0265 A 24-Hour Proteinuria Cutoff Level of 0.7 Gram After 12 Months of Treatment Best Predicts Long-Term Renal Outcome in Lupus Nephritis: Data from the Maintain Nephritis Trial. (9th June 2015) - Tamirou, F.; Lauwerys, B.R.; Dall'Era, M.; Mackay, M.; Rovin, B.; Cervera, R.; Houssiau, F.A.
Abstract : Background: Data from the Euro-Lupus Nephritis Trial (ELNT) indicated that a proteinuria <0.8g/d at 12 months after randomization is the single best predictor of good long-term renal outcome (1). Objectives: The current analysis is aimed at testing the validity of this proteinuria cutoff level in another lupus nephritis (LN) patient population, taking advantage of the long-term MAINTAIN Nephritis Trial data set (2). Methods: The MAINTAIN Nephritis Trial is an European-based randomized trial performed in 105 LN patients comparing azathioprine and mycophenolate mofetil as maintenance therapy, after induction with low-dose Euro-Lupus intravenous cyclophosphamide. Renal relapse rate was similar in the two groups and early proteinuria decrease within the first year predicted long-term renal function (2). For this analysis, aimed at defining the best cutoff proteinuria level, we selected patients with at least 7 years of follow-up for whom proteinuria measurement was available at month 3 (n=81), 6 (n=80) or 12 (n=80). Good and poor long-term renal outcome was defined as serum creatinine ≤1mg/dl and >1mg/dl at last follow-up, respectively. Sensitivity and specificity were calculated for each proteinuria level, as predictor of good long-term renal outcome. Receiver Operating Characteristic (ROC) curves (area under the curve; AUC) were drawn and the best proteinuria cutoff value at each time point was determined based on Youden index. 95% confidence intervals (CI) were calculated. Results: The best proteinuria cutoff value ( i. e. the point on the ROC curve furthest to the equality line, defined by Youden index) at month 3, 6 and 12 is indicated in the Table below, as well as their sensitivity and specificity (±95%CI) as predictor of good renal outcome. The AUCs (between 0.73 and 0.78) confirmed accuracy of the test. A proteinuria cutoff of 0.7g/day optimized sensitivity and specificity at month 12. Quite interestingly, this value is very close to the 0.8g/day at month 12 computed from the ELNT data (1). Conclusions: A 24-hour proteinuria cutoff level of 0.7 gram after 12 months of treatment best predicts long-term renal outcome in LN, confirming the ELNT data. We suggest that this target value be used as primary outcome in LN induction trials. References: Dell'Ara M et al. Predictors of Long-Term Renal Outcome in Lupus Nephritis Trials: Lessons Learned from the Euro-Lupus Nephritis Cohort. Arthritis Rheumatol 2015; in press. Tamirou F et al. Long-term follow-up of the MAINTAIN Nephritis Trial, comparing azathioprine and mycophenolate mofetil as maintenance therapy of lupus nephritis. Ann Rheum Dis 2015; in press. Disclosure of Interest: None declared